2023
DOI: 10.1002/rmv.2420
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tixagevimab‐cilgavimab as pre‐exposure prophylaxis for COVID‐19: A systematic review and meta‐analysis

Abstract: Some proportions of populations, such as immunocompromised patients and organ transplant recipients might have inadequate immune responses to the vaccine for coronavirus disease 2019 . For these groups of populations, administering monoclonal antibodies might offer some additional protection. This review sought to analyze the effectiveness and safety of tixagevimab-cilgavimab (Evusheld) as pre-exposure prophylaxis against COVID-19. We used specific keywords to comprehensively search for potential studies on Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 54 publications
4
28
0
Order By: Relevance
“…A recent meta-analysis showed that the use of tixagevimab-cilgavimab as prophylaxis was associated with decrease in COVID-19 infection rate, lower incidence of COVID-19-related hospitalizations, and decrease in severity risk. 6 In our study, it is interesting to note that none of the CAR T recipients developed breakthrough SARS-CoV-2 infections post pre-exposure prophylaxis with tixagevimabcilgavimab and most of the infected patients had prior allogeneic HSCT. CAR T recipients may have an adequate memory T-cell function with gradual reconstitution of the immune repertoire.…”
mentioning
confidence: 68%
“…A recent meta-analysis showed that the use of tixagevimab-cilgavimab as prophylaxis was associated with decrease in COVID-19 infection rate, lower incidence of COVID-19-related hospitalizations, and decrease in severity risk. 6 In our study, it is interesting to note that none of the CAR T recipients developed breakthrough SARS-CoV-2 infections post pre-exposure prophylaxis with tixagevimabcilgavimab and most of the infected patients had prior allogeneic HSCT. CAR T recipients may have an adequate memory T-cell function with gradual reconstitution of the immune repertoire.…”
mentioning
confidence: 68%
“…In contrast, their search was completed before the emergence of Omicron. Soeroto et al 45 . showed in their meta‐analysis that using tixagevimab‐cilgavimab as pre‐exposure prophylaxis against COVID‐19 may decrease the rate of SARS‐CoV‐2 infection, COVID‐19 hospitalisation and mortality rate even during Omicron variant.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, their search was completed before the emergence of Omicron. Soeroto et al45 showed in their meta-analysis that using tixagevimab-cilgavimab as pre-exposure prophylaxis against COVID-19 may decrease the rate of SARS-CoV-2 infection, COVID-19 hospitalisation and mortality rate even during Omicron variant. Our study complements this because it included a significant number of different anti-SARS-CoV-Forest plot of mortality rate in Omicron-positive patients treated with sotrovimab (experimental) and Omicron-positive patients treated with other medications (control).…”
mentioning
confidence: 99%
“…Several studies have demonstrated that COVID‐19 vaccines are the most effective strategy against any SARS‐CoV‐2 symptomatic infection and its related severe outcomes 2–4 . However, in some subpopulations such as immunocompromised patients, who may have an inadequate immune response after SARS‐CoV‐2 vaccinations, passive immunisation with preformed antibodies such as tixagevimab‐cilgavimab (Evusheld) might offer some potential benefits in providing adequate protection against COVID‐19 including the Omicron variant 5 …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] However, in some subpopulations such as immunocompromised patients, who may have an inadequate immune response after SARS-CoV-2 vaccinations, passive immunisation with preformed antibodies such as tixagevimab-cilgavimab (Evusheld) might offer some potential benefits in providing adequate protection against COVID-19 including the Omicron variant. 5 Limited available approved drugs for pregnant women and ineffective vaccines against emerging SARS-CoV-2 variants, are also problems of the COVID-19 pandemic. [6][7][8] However, pregnant women were excluded from preauthorisation clinical trials, and only limited human data on vaccine safety during pregnancy were available regarding its consequences on maternal and neonatal health.…”
Section: Introductionmentioning
confidence: 99%